Two matrix methods for solution of nonlinear and linear Lane-Emden type equations with mixed condition by operational matrix - Basirat, Behrooz; Shahdadi, Mohammad Amin (International Journal of Applied Mathematical Research, 2015)
The aim of this article is to present an efficient numerical procedure for solving Lane-Emden type equations. We present two practical matrix method for solving Lane-Emden type equations with mixed conditions by Bernstein polynomials operational matrices (BPOMs) on interval [a; b]. This methods transforms Lane-Emden type equations and the given conditions into matrix equation which corresponds to a system of linear algebraic equations. We also give some numerical examples to demonstrate the efficiency and validity of the operational matrices for solving Lane-Emden type equations (LEEs).